Penguatan Identitas Melalui Branding Kemasan dan Diversifikasi Produk Usaha Comel - Ni Nyoman Wulan Antari; Riza Wulandari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2019)
Currently a variety of strategies are strived by the entrepreneurs to strengthen their identity efforts amid new products popping up by presenting renewability in accordance with the interest that exists in the market. Partners in public service activities this is Kiki Adelya a young entrepreneur trying to do creative food products namely remahan beans and gnetum Brown named